Extracellular Signal-Regulated Kinases Phosphorylate Mitogen-Activated Protein Kinase Phosphatase 3/DUSP6 at Serines 159 and 197, Two Sites Critical for Its Proteasomal Degradation - Marchetti, Sandrine (American Society for Microbiology, 2005)
Mitogen-activated protein (MAP) kinase phosphatases (MKPs) are dual-specificity phosphatases that dephosphorylate phosphothreonine and phosphotyrosine residues within MAP kinases. Here, we describe a novel posttranslational mechanism for regulating MKP-3/Pyst1/DUSP6, a member of the MKP family that is highly specific for extracellular signal-regulated kinase 1 and 2 (ERK1/2) inactivation. Using a fibroblast model in which the expression of either MKP-3 or a more stable MKP-3-green fluorescent protein (GFP) chimera was induced by tetracycline, we found that serum induces the phosphorylation of MKP-3 and its subsequent degradation by the proteasome in a MEK1 and MEK2 (MEK1/2)-ERK1/2-dependent manner. In vitro phosphorylation assays using glutathione S-transferase (GST)-MKP-3 fusion proteins indicated that ERK2 could phosphorylate MKP-3 on serines 159 and 197. Tetracycline-inducible cell clones expressing either single or double serine mutants of MKP-3 or MKP-3-GFP confirmed that these two sites are targeted by the MEK1/2-ERK1/2 module in vivo. Double serine mutants of MKP-3 or MKP-3-GFP were more efficiently protected from degradation than single mutants or wild-type MKP-3, indicating that phosphorylation of either serine by ERK1/2 enhances proteasomal degradation of MKP-3. Hence, double mutation caused a threefold increase in the half-life of MKP-3. Finally, we show that the phosphorylation of MKP-3 has no effect on its catalytic activity. Thus, ERK1/2 exert a positive feedback loop on their own activity by promoting the degradation of MKP-3, one of their major inactivators in the cytosol, a situation opposite to that described for the nuclear phosphatase MKP-1.